Major Cardiovascular Advances: Highlights from the 2019 American College of Cardiology Annual Scientific Session - Hisham A Badreldin; Khalid bin Saleh; Majed Al Yami (US Cardiology Review)
The 69th American College of Cardiology Annual Scientific Session and Expo was held in New Orleans, Louisiana on March 16–18, 2019. For many years this meeting has gathered together an enormous number of participants, abstracts, oral presentations, poster presentations, educational sessions, late-breaking clinical trial results, and clinical practice guidelines under one roof. The authors have selected and summarized the key points from a number of key landmark trials, featured clinical research results and clinical practice guidelines that were presented during this year’s meeting.